Pennsylvania Whiskey Rebellion collection
Correspondence, reports, depositions, petitions, tax lists, minutes of meetings, and other papers relating to the 1794 whiskey excise tax rebellion in western Pennsylvania. Includes printed and manuscript reports to the president and secretary of state by the commission appointed by President Washington to attempt to settle the rebellion and numerous petitions sent by individuals and townships submitting to the tax. Correspondents include William Bradford, George Clymer, Albert Gallatin, Charles Lee, Thomas Mifflin, James Ross, and Jasper Yeates.
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
Collection material in English.
Keywords: Bradford, William, -- 1755-1795 -- Correspondence; Clymer, George, -- 1739-1813 -- Correspondence; Gallatin, Albert, -- 1761-1849 -- Correspondence; Lee, Charles, -- 1758-1815 -- Correspondence; Mifflin, Thomas, -- 1744-1800 -- Correspondence; Ross, James, -- 1762-1847 -- Correspondence; Washington, George, -- 1732-1799.; Yeates, Jasper, -- 1745-1817 -- Correspondence; Whiskey Rebellion, Pa., 1794.; Taxation -- Pennsylvania